Secure deployment strategy of virtual machines based on operating system diversity - Miao ZHANG; Xin-sheng JI; Jian-jian AI; Wen-yan LIU; Hong-chao HU; Shu-min HUO (网络与信息安全学报)
The resource-sharing model for cloud computing raises many security issues,such as co-resident of virtual machines,while greatly improving resource utilization.In particular,when a user adopts a single operating system,an attacker can steal privacy and data by compromising the user's entire virtual machine at a smaller cost.In view of this security threat,a strategy for the security deployment of virtual machine based on operating system diversity was presented.This method firstly recommended an operating system configuration options for users applying for virtual machines with the highest degree in diversity,and then through the secure deployment strategy,maximized the effect of diversity,thus making the attacker pay more cost.The experimental results show that compared with the method of single operating system,this method can reduce the attack efficiency by 33.46% at least.